2020
DOI: 10.1136/bmjopen-2020-040573
|View full text |Cite
|
Sign up to set email alerts
|

Development of a risk prediction model of potentially avoidable readmission for patients hospitalised with community-acquired pneumonia: study protocol and population

Abstract: Introduction30-day readmission rate is considered an adverse outcome reflecting suboptimal quality of care during index hospitalisation for community-acquired pneumonia (CAP). However, potentially avoidable readmission would be a more relevant metric than all-cause readmission for tracking quality of hospital care for CAP. The objectives of this study are (1) to estimate potentially avoidable 30-day readmission rate and (2) to develop a risk prediction model intended to identify potentially avoidable readmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
8
1
Order By: Relevance
“…Mounayar reported that the readmission rate for community-acquired pneumonia was 17.5%, which was lower than our result [ 14 ]. One reason for this may be the higher readmission rate at our hospital, which is an acute care facility.…”
Section: Discussioncontrasting
confidence: 91%
“…Mounayar reported that the readmission rate for community-acquired pneumonia was 17.5%, which was lower than our result [ 14 ]. One reason for this may be the higher readmission rate at our hospital, which is an acute care facility.…”
Section: Discussioncontrasting
confidence: 91%
“…The study cohort was defined using both demographics and clinical-related criteria from prior work involving readmission analysis in a pneumonia setting [6,25,26]. The study cohort included all adult patients (aged ≥ 18 years) who had an index (first) hospitalization from January 1, 2016, through November 31, 2016, with a principal inpatient diagnosis of pneumonia using the International Classification of Diseases, Tenth Revision, codes (J10.0, J10.1, J10.8, J11.0, J11.1, J11.8, J12.0, J12.1, J12.2, J12.3, J12.8, J12.9, J13, J14, J15.x, J16.0, J16.8, J17.0, J17.1, J17.2, J17.3, J17.8, J18.0, J18.1, J18.2, J18.8, J18.9, J69.0, B01.2, B20.6, B25.0, B59) [27,28] between January 1, 2016, and November 30, 2016.…”
Section: Study Populationmentioning
confidence: 99%
“…From all available data elements recorded in the NRD data and based on prior NRD studies involving readmission analysis [6,12], a total of 61 clinically pertinent variables were included for ML model development, including (1) demographics (age, and sex); (2) socioeconomic status (race, expected primary payer, and median household income); (3) healthcare use indicator (number of diagnoses recorded, number of procedures recorded, number of external causes recorded, indicator of emergency service, and indicator of operating room use); (4) comorbid conditions included conditions in the Elixhauser Comorbidity Index [30], and other pneumoniarelated conditions operationalized based on literatures [6,26,31]; (5) composite score (NRD's severity measures classified by the 3M All-Patient Refined Diagnosis-Related Group (DRG) severity score), and Elixhauser comorbidity index score [30]); (6) admission/discharge specific factors (discharge month, resident status, and discharge disposition); (7) hospital-level characteristics (control/ownership of hospital, size of hospital, teaching status of hospital, and hospital urban/rural location). Specifically, baseline comorbid conditions were identified based on AHRQ HCUP Elixhauser Comorbidity Software using ICD-10-CM diagnosis codes [32].…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Most patient-specific models focused on heart conditions [ 55 72 ]. The remaining studies worked on readmission among patients with diabetes [ 73 79 ], psychiatric conditions [ 80 83 ], TJA [ 84 , 85 ], COPD [ 86 , 87 ], CABG [ 88 , 89 ], and pneumonia [ 90 ].
Fig.
…”
Section: Application To Readmissionmentioning
confidence: 99%
“…Even with the emergence of the ML algorithm, 29 out of 36 articles adopted traditional statistical methods. Among these studies, ~ 90% used LR either as a baseline [ 56 , 58 , 60 , 62 64 , 68 , 73 , 74 , 76 78 , 83 , 85 87 ] or the main model in prediction [ 60 , 69 , 71 , 82 , 88 90 ], and 3 studies derived their own risk scores on the basis of LR variable coefficients [ 61 , 66 , 84 ]. In the remaining 3 papers, the prognosis of readmission was carried out with Cox regression survival analysis.…”
Section: Application To Readmissionmentioning
confidence: 99%